Starter driving semiconductor switch apparatus - HATA TOSHIAKI; TANAKA TAKAAKI; TAKAHASHI YASUHIRO; KUBO TORU; UMEMOTO HIDEKI (2014)
A starter driving semiconductor switch apparatus energizes and de-energizes a starter according to a command from an outside. A series circuit to which semiconductor switches are connected in series is provided between a battery serving as a power supply and the starter. The starter is energized by bringing all the semiconductor switches into conduction. A voltage or a current at a predetermined point in the series circuit is monitored to make a self-diagnosis on whether the starter is allowed to start and whether there is a failure in the semiconductor switches according to a monitor output. The starter driving semiconductor switch apparatus is thus expected to have a longer useful life by energizing the starter not by using mechanical contacts but by using semiconductor switches.